ACTIVITY OF CELLULASE IN THE MIDGUT HOMOGENATE OF THE PALM WEEVIL, RHYNCHOPHORUS PHOENICIS F. (COLEOPTERA: CURCULIONIDAE) - Omotoso, O.T. (Acta Scientiae et Intellectus, 2024)
Palm weevil, Rhynchophorus phoenicis F is a key pest of palm trees and sugar cane in the tropics and subtropical regions of the world where it causes great economic losses. The midgut of the larva and adult stages of this insect are rich in digestive enzymes. Cellulase, being one of the most important carbohydrases was investigated in the midguts of the larva and adult stages of this insect using dinitrosalicylic acid reagent method. The optimum condition for cellulase bioassay in the midgut of the larva of R. phoenicis involved 2 ml of 1% starch, 2 ml of phosphate buffer (pH 4.0) and 1 ml of enzyme extract incubated at optimum temperature of 45o C were optimal for cellulase activity in both the larval and adult weevils. Michaelis- Menten constants (Km) of 2.5 mg/ml and 3.12 mg/ml were obtained for the larva and adult midgut cellulases respectively.